Analysis of Voice Signals Change by Voice Modulation Program - Hyun Kim, Bong; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: Voice modulation is used in various fields. Especially, it is widely used in entertainment program for voice tampering to give viewers fun, and voice tampering to guarantee the victim 's identity in news. However, in recent years, voice tampering has been exploited for crime. As the information and communication technology in the information society has developed rapidly, the crime using voice modulation is increasing.Methods/Statistical analysis: Therefore, in this paper, the change of voice signal is analyzed by analyzing both normal voice and modulated voice. For this purpose, general voice was collected using the same place, time, microphone, etc., and a modulated voice was collected by applying a voice modulation program. In addition, various voice analysis parameters such as spectrum, formant, intensity, pitch, pulse, jitter, shimmer, DoVB, and NHR were applied to the study.Findings: Experimental results show that the difference between the normal voice and the modulated voice is caused by various voice signal analysis parameters due to voice modulation. Especially, in the modulated voice, the spectrum, pitch, and DoVB values were decreased as compared with the general voice. In addition, jitter, shimmer, and NHR values resulted in a result that the modulated voice was higher than the normal voice. There was no significant difference in strength, formant and pulse measurements. Based on the results of this study, it is possible to reflect the changed voice analysis parameters by the voice modulation program.Improvements/Applications: Voice modulation is useful in various aspects such as fun and identification. However, it has been recently exploited in the same way as voice phishing. Therefore, in this paper, we measured the voice analysis parameters that are changed by the voice modulation program. Based on this, we compared and analyzed the general voice and the modulated voice and extracted the pattern of the voice signal changed by the voice modulation.Â